2017
DOI: 10.3390/nu9080912
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Stress and Appetite Responses in Male Power-Trained Athletes during Intensive Training Camp

Abstract: An intensive consecutive high-volume training camp may induce appetite loss in athletes. Therefore, this study aimed to investigate the changes in stress and appetite responses in male power-trained athletes during an intensive training camp. The measurements at Day 2 and at the end of a 9-day intensive training camp (Camp1 and Camp2, respectively) were compared with those of the resting period (Rest) and the regular training period (Regular; n = 13). The stress state was assessed based on plasma cortisol leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In our study, an increased cortisol level (Table 1) probably resulted from the fact that the study subjects trained intensively and played matches throughout the experiment. Such conditions are undoubtedly conducive to the occurrence of stress, both physical and mental, resulting from training and competition [42,43]. Under such conditions, there is a significant secretion of cortisol in the adrenal glands, which undoubtedly increases catabolism and inhibits the regeneration process [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, an increased cortisol level (Table 1) probably resulted from the fact that the study subjects trained intensively and played matches throughout the experiment. Such conditions are undoubtedly conducive to the occurrence of stress, both physical and mental, resulting from training and competition [42,43]. Under such conditions, there is a significant secretion of cortisol in the adrenal glands, which undoubtedly increases catabolism and inhibits the regeneration process [42].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that supplementation with high doses of 5000-10,000 IU/day of vitamin D 3 is effective in treating athletes with 25(OH)D deficiency [9,14,42]. Soccer is characterized by the continuous combination of short sprints, rapid accelerations/decelerations and changes of direction interspersed with jumping, kicking, tackling and informal times for recovery [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Although appetite is supposedly suppressed after strenuous training, there was no difference in appetite after high-intensity training in the previous study on athletes (Oshima et al, 2017). Training itself seems to have no effect on the appetite of athletes who undertake continuous training.…”
Section: Meal Frequency and Appetitementioning
confidence: 60%
“…Visual analog scale (VAS) was used to subjectively evaluate appetite (Oshima et al, 2017). The subjects were asked to record their degree of satiety before every meal during the trials, on a 100mm VAS ranging from very full to very hungry.…”
Section: Appetitementioning
confidence: 99%
“…Positive correlation between psychological stress and cortisol levels and negative association between psychological stress and SIgA levels [31]. Oshima et al reported acute physiological training stress was observed an increase in plasma resting cortisol concentration [32]. He et al reported that signi cant decreases in secretion rates concentrations of sIgA was observed at times of intense training and competition [33].…”
Section: Discussionmentioning
confidence: 99%